P48 Virtual reality fully immersive interactive technology. Can this improve medical students' preparedness for resuscitation?. (November 2018) - Judd, Thomas; Young, Alexander
Abstract : Background: Over 60% of 4th year medical students lack confidence in dealing with cardiac arrest situations. 1 Also, over 35% of final year medical students felt reluctant to participate in resuscitation as they felt unprepared. 2 Recent technology advancements allow a smartphone to be converted into a virtual reality headset. We have developed a method of Virtual Reality Fully Immersive Interactive Technology Teaching (VR FIITT) where a student may be fully immersed in a virtual reality teaching scenario. Method: 75 preclinical prior to cardiopulmonary resuscitation (CPR) training were recruited into the study. They were randomly assigned to 5 groups: VR FIIT CPR, textbook learning, video training, course training, blended teaching method (textbook, video and course training). Each group was provided 20 min of training via their designated training method. After which they were asked to rank their confidence to perform the technical steps of CPR on a real patient, their enjoyment of the teaching method and their confidence to perform this skill in a real environment under pressure, using a Likert scoring chart. Results: VR FIITT scored highest in all three areas of assessment compared to the other teaching methods. Students enjoyed the VR FIITT (p=0.028) and had more confidence to use their skills in clinical practice (p=0.045) compared to all other teaching methods. However it was only shown to be superior to Video and textbook teaching methods (p=0.036) when assessing how confident students felt with the steps of CPR. Discussion and conclusion: VR FITT has been shown to be a more enjoyable method of learning for students. Students that have been taught using this teaching method felt better prepare to use their clinical skills in a real environment under pressure. The nature of resuscitation events is a main factor in why medical students feel underprepared to attend resuscitation calls as a newly qualified junior doctor. This project highlights this technology can be used to address this issue. By helping to reduce anxiety, and potentially improve performance, when faced with these events in real life. References: Graham CA, Guest KA, Scollon D. Cardiopulmonary resuscitation. Paper 2: a survey of basic life support training for medical students. J Accid Emerg Med1994;11(3):165–167. Pillow MT, Stader D, Nguyen M, Cao D, McArthur R, Hoxhaj S. Perceptions of basic, advanced, and pediatric life support training in a United States medical school. J Emerg Med2014;46(5):695–700.